Characteristics and challenges of pesticide spray applications in Mato Grosso, Brazil - Carvalho, Fernando Kassis; Chechetto, Rodolfo Glauber [UNESP]; Mota, Alisson Augusto Barbieri; Antuniassi, Ulisses Rocha [UNESP] (Research Information, 2017)
Brazil is now one of the world’s largest exporters of grains, particularly for crops such as soybean (Glycine max) and corn (Zea mays). It gained prominence in international commodities trading with large exports to several countries, including China and some European countries. With tropical weather and no low temperatures during the winter, commonly two crops can be grown in a year. As an example, in the season of 2016/2017, Brazilian soybean production it is expected to be about 95 million tons and corn 68 million tons (Conab, 2016). The state of Mato Grosso (MT), located in Midwestern Brazil is one of the agricultural regions of great importance for the production of grains and fiber, representing about 23% of the national production, with a harvest of 211 million tons forecast in the 2016/2017 harvest. The planted area in that state is larger than that of Spain, or about 27 million hectares. The climate, although allowing cultivation during all seasons, also favours the development of pests, diseases and weeds, and these do not have their growth cycles interrupted in the winter. To maintain high levels of productivity, crop protection is essential, so sprays are applied when necessary during the development of crops. The Mato Grosso has extensive flat areas, commonly with farms ranging in size from 5 to 50 thousand hectares. This allows use of large self-propelled sprayers operated at high speeds, often over 20 km h-1. In this region of Brazil, it is also common to use aircraft as an alternative and/or complement to ground applications. Spray drift is a major concern, due to the meteorological conditions during spray application. Hence the need to select spray nozzles carefully. There is a major concern in Brazil to instruct farmers to use nozzles with drift reducing technologies (DRTs), such as air induction and pre-orifice nozzles, especially for spraying systemic herbicides, when coverage and penetration are not essential. Also, when applications are next to sensitive areas (water supplies, forests, cities or villages, sensitive crops), the recommendation is to increase droplet size. It can be achieved by selecting the mentioned nozzles instead of cone and twin-fan nozzles (commonly used for better coverage and penetration), which generate fine or very fine droplets. Increasing application rate, selecting drift reduction adjuvants and respecting the recommended meteorological conditions for an application are also important strategies in these circumstances. In view of this, great efforts have been made during the last few years to improve responsibility and sustainability while spraying, by training courses, presentations and development of rural extension programs for ground applications. A voluntary certification program for aerial applicators, called “Sustainable Agricultural Aviation Certification” has also been introduced. The existing pressure to increase the operational efficiency of sprayers (hectares per hour) has created a tendency to use lower application rates (L ha-1). The risk of using small droplets has to be counteracted by correct nozzle selection. Thus, knowledge about the application technology has great importance to maintain the balance between the performance and the environmental safety of applications.
Keywords: Drift reduction; Spray nozzles; Sustainably; Tank mixes